THE EFFECT OF WEATHERING ON WOOD AND ITS PROTECTION - Hien Mai, Trinh; Thi Kim Hong, Tang; Thi Yen, Nguyen (Journal of Forestry Science and Technology, 2021)
When wood and wood products is exposed outdoor, above ground, it undergoes many complex processes such as: photo-degradation by ultraviolet and visible light; leaching, hydrolysis and swelling/shrinking by water/moisture (railfall, dew, snow, changes in humidity in the air); discoloration by staining fungi and molds. All of the above effects reduce the use and life-time of wood products. The appearance of unprotected wood changes considerably after only few months of wood’s weathering exposure. To protect wood from deterioration by weathering, the most common way is to prevent weathering factors from reaching the wood. Wood coatings including paints, stains, and similar materials provide good protection to wood by partly or completely obstructing the light to reach wood and excluding water from wood. Wood preservatives such as chromated copper arsenate (CCA), ammoniacal copper quat (ACQ), acid copper chromate (ACC), mainly protect wood from damages by microorganism. Chemical modification of wood may cause change in wood properties, hence improve weathering resistance significantly. This paper discussed the influence of outdoor weathering including photo degradation, water/moisture degradation and fungal degradation on the performance of wood in detail. The chemical and physical changes of wood exposed outdoors are described, and methods for protecting exposed wood surfaces are summarized.